2008
DOI: 10.1007/s12033-007-9029-0
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Expression of Human Cytomegalovirus Glycoprotein B (UL55) in the Seeds of Homozygous Rice Plants

Abstract: Production of recombinant subunit vaccines in transgenic plants may be a means of reducing vaccine costs while increasing availability and safety. A plant-derived product found safe and effective for oral administration would provide additional advantages when used as a vaccine. Outstanding issues with the technology include transgene stability through successive generations and consistent bioproduction. We previously reported expression of glycoprotein B (gB) of human cytomegalovirus in seeds of transgenic to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…They successfully elicited specific antibodies in mice immunized intraperitoneally with transgenic rice plant extracts together with Freund's adjuvant. Tackaberry et al (2008) reported the expression of glycoprotein B of human cytomegalovirus (CMV) in transgenic rice seeds and suggested a new possibility for prevention of CMV infection, although the efficacy of vaccination in vivo was not reported. After the initial infection, CMV establishes lifelong latency in human cells, especially cells of the myeloid lineage (Gandhi and Khanna 2004).…”
Section: Rice-based Vaccines For Infectious Diseasesmentioning
confidence: 99%
“…They successfully elicited specific antibodies in mice immunized intraperitoneally with transgenic rice plant extracts together with Freund's adjuvant. Tackaberry et al (2008) reported the expression of glycoprotein B of human cytomegalovirus (CMV) in transgenic rice seeds and suggested a new possibility for prevention of CMV infection, although the efficacy of vaccination in vivo was not reported. After the initial infection, CMV establishes lifelong latency in human cells, especially cells of the myeloid lineage (Gandhi and Khanna 2004).…”
Section: Rice-based Vaccines For Infectious Diseasesmentioning
confidence: 99%
“…The full-length HCMV gB protein of the Towne strain had already been successfully expressed as a membrane protein in the protein storage vesicles of tobacco and rice seeds, representing about 1% of total seed protein, but no biochemical characterization was reported [28,29,30,31]. Here, we produced the gB ectodomain from the AD169 strain in N. tabacum BY-2 transgenic cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…In plants, the seed serves as a storage organ that is also required for the establishment of the new generation . It has been shown that throughout the dormancy and storage periods of the rice seed, its storage proteins remain intact and functional (Tackaberry et al 2008) and heterologous proteins are also stable in seeds for 2-3 years. This is a considerable advantage over plant cell platforms that accumulate protein in leafy tissue (e.g., tobacco), as they are more prone to hydrolytic inactivation and have much shorter shelf lives.…”
Section: Introductionmentioning
confidence: 99%